Pendampingan Pengembangan Usaha Kecil Menengah (Jahe Bubuk Istan) Melalui Pemanfaatan Teknologi Digital Desa Tegalrejo Kecamatan Pulung Ponorogo - Mariana Mariana; Chazwatul Wakidah (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The assistance programisting in the in this community is micro, smaal an medium enterprises UMKM assisting in the manufacture of istan ginger powder in the village of Tegalrejo,pulungsub-disrict,ponorogo ditrict, the problems the face are related to assistance in the manufacture of istan ginger powder,this assistance program is aimed at assisting an strengthening the community through micro,small and medium enterprises the medium method used to overcome this problem is education to the community through assistance in making ginger powder istan.through which it is formed into a solution in overcoming the problem at hand.ginger is one of the spices and medicinal commodities which is the priority plant in findings.the use f preparations because apart from having a delicious and distinctive taste and aroma,it also has a function,increase appetite,strengthens the stomach and prevents infection.the prodct development of istan ginger powder,in various forms of finished products is very profitable,processed ginger products have been windeiy circulated in the market for products including istan cooking seasoning, syrup,ginger candy and istan red ginger powder.